2006
DOI: 10.1007/s11295-005-0029-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a full-length CC–NBS–LRR resistance gene analog candidate from sugar pine showing low nucleotide diversity

Abstract: The nucleotide-binding-site and leucine-richrepeat (NBS-LRR) class of R proteins is abundant and widely distributed in plants. By using degenerate primers designed on the NBS domain in lettuce, we amplified sequences in sugar pine that shared sequence identity with many of the NBS-LRR class resistance genes catalogued in GenBank. The polymerase chain reaction products were used to probe a cDNA library constructed from needle tissue of sugar pine seedlings. A full-length cDNA was obtained that demonstrated high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…A previously cloned Pinus lambertiana NBS-LRR gene is highly conserved, even between sugar pine and WWP (Jermstad et al 2006). Although an AFLP-based method was useful in discovering RGA-related DNA markers specific to disease resistant trees Ekramoddoullah 2007, 2008), it is still a challenge to identify full-length RGAs and to elucidate their genetic variation and molecular role in disease resistance in a conifer pathosystem.…”
Section: Discussionmentioning
confidence: 99%
“…A previously cloned Pinus lambertiana NBS-LRR gene is highly conserved, even between sugar pine and WWP (Jermstad et al 2006). Although an AFLP-based method was useful in discovering RGA-related DNA markers specific to disease resistant trees Ekramoddoullah 2007, 2008), it is still a challenge to identify full-length RGAs and to elucidate their genetic variation and molecular role in disease resistance in a conifer pathosystem.…”
Section: Discussionmentioning
confidence: 99%
“…In sugar pine, the R gene associated with a hypersensitive reaction (HR) response has been mapped by proximity to six markers (D evey et al. 1995; also see J ermstad et al. 2006), thereby providing a beginning point for gene cloning.…”
Section: Pathology and Ecologymentioning
confidence: 99%
“…The reports also suggested that the R genes from conifers and angiosperms share common ancestry and were under diversifying selection and/or neutral selection (Liu and Ekramoddoullah 2003). Subsequently, a 2.9 kb CC-NBS-LRR subclass of RGA with low nucleotide polymorphism in the NBS-LRR domain was reported by Jermstad et al (2006)The gene was 58 times less variable than other R genes from conifers. This suggested that the gene acted as 'guardee' protein which generally maintains low number of alleles in the populations (Maurico et al 2003;McDowell 2004).…”
Section: Hydrolysis Of Chitinmentioning
confidence: 99%